2022
DOI: 10.3390/app12178753
|View full text |Cite
|
Sign up to set email alerts
|

Design of an In-Process Quality Monitoring Strategy for FDM-Type 3D Printer Using Deep Learning

Abstract: Additive manufacturing is one of the rising manufacturing technologies in the future; however, due to its operational mechanism, printing failures are still prominent, leading to waste of both time and resources. The development of a real-time process monitoring system with the ability to properly forecast anomalous behaviors within fused deposition modeling (FDM) additive manufacturing is proposed as a solution to the particular problem of nozzle clogging. A set of collaborative sensors is used to accumulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 28 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…These systems provide real-time feedback and enable modification of process parameters during printing. A study has proposed the use of sensors and machine learning algorithms to prevent nozzle clogging, achieving an impressive prediction accuracy rate of 97.2% for the future state of the 3D print [213]. Such systems aim to eliminate the need for operator monitoring and enhance print success.…”
Section: In-process Monitoringmentioning
confidence: 99%
“…These systems provide real-time feedback and enable modification of process parameters during printing. A study has proposed the use of sensors and machine learning algorithms to prevent nozzle clogging, achieving an impressive prediction accuracy rate of 97.2% for the future state of the 3D print [213]. Such systems aim to eliminate the need for operator monitoring and enhance print success.…”
Section: In-process Monitoringmentioning
confidence: 99%
“…One common printing error is nozzle clogging [ 13 , 14 ]. In order to minimize this detrimental issue, numerous efforts have been made by researchers to overcome nozzle clogging during the printing process [ 13 , 21 , 22 ]. Gutierrez et al proposed a method to decrease the clogging deposition rate of alumina inclusions in continuous casting nozzles through three simultaneous measures: flow modification, the use of raw materials with a low impurity content, and smoothed internal surfaces [ 13 ].…”
Section: Experimental Workmentioning
confidence: 99%
“…Plant studies with these nozzles, together with water modeling showed that the current strategy may significantly reduce clogging occurrence. More recently, as a response to the problem of nozzle clogging, Sampedro et al created a real-time process monitoring system capable of accurately forecasting abnormal behaviors in the FDM printing method [ 21 ]. A network of collaborative sensors was utilized to collect time series data, which were then processed by the suggested machine learning method.…”
Section: Experimental Workmentioning
confidence: 99%
“…By recording data with sensors [23] within a soundproof room [24], the ANN can anticipate future signals and vibrations, thereby identifying print results and avoiding filament damage. In conclusion, the integration of machine learning techniques [17] into 3D printing monitoring systems has the potential to significantly improve the reliability, efficiency, and quality of the additive manufacturing process [25]. By effectively detecting and predicting machine conditions, manufacturers can reduce the likelihood of failures and optimize their operations for maximum output and quality.…”
Section: Introductionmentioning
confidence: 99%